Outcomes of hematopoietic cell transplantation using donors or recipients with inherited chromosomally integrated HHV-6 - Hill, Joshua A; Magaret, Amalia S; Hall-Sedlak, Ruth; Mikhaylova, Anna; Huang, Meei-Li; Sandmaier, Brenda M; Hansen, John A; Jerome, Keith R; Zerr, Danielle M; Boeckh, Michael (Blood, 2017)
Human herpesvirus 6 (HHV-6) species have a unique ability to integrate into chromosomal telomeres. Mendelian inheritance via gametocyte integration results in HHV-6 in every nucleated cell. The epidemiology and clinical effect of inherited chromosomally integrated HHV-6 (iciHHV-6) in hematopoietic cell transplant (HCT) recipients is unclear. We identified 4319 HCT donor-recipient pairs (8638 subjects) who received an allogeneic HCT and had archived pre-HCT peripheral blood mononuclear cell samples. We screened these samples for iciHHV-6 and compared characteristics of HCT recipients and donors with iciHHV-6 with those of recipients and donors without iciHHV-6, respectively. We calculated Kaplan-Meier probability estimates and Cox proportional hazards models for post-HCT outcomes based on recipient and donor iciHHV-6 status. We identified 60 HCT recipients (1.4%) and 40 donors (0.9%) with iciHHV-6; both recipient and donor harbored iciHHV-6 in 13 HCTs. Thus, there were 87 HCTs (2%) in which the recipient, donor, or both harbored iciHHV-6. Acute graft-versus-host disease (GVHD) grades 2-4 was more frequent when recipients or donors had iciHHV-6 (adjusted hazard ratios, 1.7-1.9; = .004-.001). Cytomegalovirus viremia (any and high-level) was more frequent among recipients with iciHHV-6 (adjusted HRs, 1.7-3.1; = .001-.040). Inherited ciHHV-6 status did not significantly affect risk for chronic GVHD, hematopoietic cell engraftment, overall mortality, or nonrelapse mortality. Screening for iciHHV-6 could guide donor selection and post-HCT risk stratification and treatment. Further study is needed to replicate these findings and identify potential mechanisms.